PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PRODUK MAKANAN KEMASAN TANPA IZIN EDAR YANG BEREDAR DI PASARAN - Desy Lestari, Suradi, Rinitami Njatrijani*) (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
In this globalization era appears on market many kinds of marks, types, sizes, tastes, and prices of food productions. They had passed quality control of procedures, terms, and conditions to be able to market and to consume. One of the terms and conditions is to state the product distribution number of product usage. It must be applied to assure customer about quality, health, and nutrient of the products. However, in reality there are still lots of disobediences to the regulation of Indonesian Law (UU no.8 Tahun 1999) about consumer protection. The spread of unregistered packed foods on the market is getting worst nowadays, and they could be easily found in supermarkets or traditional markets. It seems that the doers of that disobedience are careless about the rights of customers and mindless about the regulation of consumer protection.The analyzed issues of this thesis are: (1) How the law protects consumers who consume unregistered food products that spread easily on the market? (2) How the government reacts in regulating, supervising, and releasing the distribution number of product usage? (3) How the government applies punishment to people, in this case are producers or distributors who sell or distribute unregistered food products on the market?This research used juridical empirical approach method. The correspondences of the data source are Foods and Medicine Control Center of Semarang through Consumer Information Services and Investigation Staff of Foods and Medicines Control Center in Semarang. The collected data are primary, which are collected from interview process, and secondary data. This research used also analytical method which is analyzed by using qualitative method. The result of this research shows that the government has established regulation about spreading of unregistered food products. The government formed also Foods and Medicines Control Center to control, supervise, and release the registration number for packed food products based on the recent Indonesian law and regulation. Efforts of the Foods and Medicines Control Center are pre-market control, which is a control before products are distributed to the market, and post-market control, which is a control after products are distributed to the market. Sanctions for the criminal doers are criminal sanctions, civil sanctions, and administrative sanctions based on Indonesian Law No. 8 year 1999 about Consumer Protection and No. 7 year 1996 about foods.